The Impact of Religious Doctrine on Legal Compliance: An Analytical Study in Light of Legal Philosophy - Smail, تحسین (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
The established sources of legal obligation are fivefold, encompassing both voluntary and involuntary origins. Beyond these, secondary sources also contribute to legal adherence, with religious belief potentially serving as one such source. This belief can render a devout individual generally committed and specifically compliant with their obligations, including legal ones. However, challenges arise in determining whether this source is voluntary or involuntary: does the individual adhere to obligations by free will, or is it driven by oversight, a higher power, or fear compelling the soul to comply with the law out of concern for judgment day? This could result in the religious person fulfilling obligations under duress, without genuine volition. Alternatively, there might be a philosophy underpinning this personal legal commitment by the believer, possibly rooted in conscience, the duality of good and evil, or the principle of reward and punishment. These issues and their examination are the focus of this study.